Tryptophan breakdown is increased in euthymic overweight individuals with bipolar disorder: a preliminary report. (12th December 2013) - Reininghaus, Eva Z; McIntyre, Roger S; Reininghaus, Bernd; Geisler, Simon; Bengesser, Susanne A; Lackner, Nina; Hecht, Karen; Birner, Armin; Kattnig, Fabian; Unterweger, Renate; Kapfhammer, Hans‐Peter; Zelzer, Sieglinde; et al.
<x xml:space="preserve">Abstract</x> Objectives Individuals with bipolar disorder (BD) are disproportionately affected by symptoms of being overweight and metabolic syndrome when compared to the general population. The pertinence of this observation is underscored by observations that excess weight is associated with a more complex illness presentation, course, and outcome in BD. We present the first preliminary report of our BIPFAT study, which explored shared hypothesized pathophysiological pathways between being overweight and having BD. Methods We investigated the tryptophan–kynurenine metabolism pathway as a proxy of dysregulated inflammatory homeostasis in euthymic, overweight individuals with BD (n = 78) compared to healthy controls (n = 156). Results Both blood kynurenine concentrations and the kynurenine to tryptophan ratio [(Kyn:Trp); an estimate of tryptophan breakdown] were significantly higher in the total sample of euthymic patients with BD, with greater increases noted in both parameters in the subsample of overweight patients with BD. When compared to controls, peripheral neopterin concentrations were significantly lower. Within the BD group, there were also significant between‐group differences in neopterin concentrations, with higher levels in those who were overweight and in subjects with BD in the later stages of illness compared to earlier stages. Conclusions Increased tryptophan breakdown, as well as neopterin levels in BD, may be an indirect mediator of immune‐mediated inflammation. In BD, this may account for the high prevalence of medical comorbidities and increased mortality. The observation of increased kynurenine levels and Kyn:Trp, and altered circulating neopterin levels provides indirect evidence of increased activity of tryptophan‐degrading indoleamine 2, 3‐dioxygenase in euthymic individuals with BD, underscoring the role of inflammatory mediators as a causative and/or consequent factor. More robust abnormalities in the overweight subsample underscore the additional inflammatory burden of medical comorbidity and suggest a shared pathophysiology as well as a mechanism mediating BD and cardiovascular disease.